Effect of Heavy Metal Pollution on Leaf Litter Decomposition of Two Species of Mangroves, Avicennia marina and Rhizophora mucronata - Waqar Ahmed ,; S. Shahid Shaukat, (Journal of Basic & Applied Sciences, 2021)
Decomposition of litter is influenced by physicochemical characteristics of the habitat which is affected by pollution. In this study the effect of heavy metals on leaf litter decomposition of two mangrove species, Avicennia marina and Rhizophora mucronata is investigated. An experiment was conducted in which litter bags were half-buried in mangrove soil in earthen pots in a greenhouse in which close to natural conditions were maintained and they were treated with 0, 5 and 10 ppm Ni and Pb as a solution of sea water for 16 weeks. Periodic observations were taken on the dry weight remaining and the four factor ANOVA was performed. All four factors (species, heavy metals, concentrations, time) were found to be significant (P at the most 0.05) while some of the interactions were also significant. Half-life and rate of decomposition, k were calculated on the basis of 12 periodic weight loss observations. The litter decomposition followed an exponential decay curve in all cases. The highest rate of decomposition (0.0155 gDWd-1) and the shortest half life (7.44 days) were found for the control of Avicennia marina. In general, decomposition rate of A. marina was more rapid compared to that of R. mucronata. Whereas, the decomposition in treatments with heavy metals were found to be slower than in the controls, the minimum of which (0.0105 gDWd-1) and the longest half life (18.17 days) were found in Rhizophora mucronata leaves treated with 10 ppm Pb. Lead appears to be more inhibitory to the process of litter decomposition compared to nickel. The two mangrove species responded differentially to the heavy metal concentrations. The influence of heavy metals in the decomposition process is discussed.